The Effect of Mud Pack Treatment in Knee Osteoarthritis - Ersin Odabaşı,; Mustafa Turan,; Hakan Erdem,; Salih Pay,; Mahir Güleç,; Müfit Zeki Karagülle, (Archives of Rheumatology, 2009)
Objective: The aim of this study was to evaluate the efficacy of mud pack treatment in patients with knee osteoarthritis (OA). Material and Methods: Fifty-seven patients with bilateral primary OA of the knee were enrolled in the study. Patients were divided into two groups based on their availability for mud application during the study period. The patients in the study group (32 patients) were subjected to daily mud pack treatment on weekdays only for three weeks, applied to both knees for 30 minutes (min) at 45°C (total 15 applications). Mud applications were done in the musculoskeletal outpatient clinic by the same person. The patients in the control group (25 patients) had analgesic treatment with acetaminophen 2 g/day. All patients were evaluated three times by assessors who were blinded to both the intervention and evaluation period: (1) at the baseline, (2) immediately after the 15th application, and (3) 30 days after the end of the treatment. Western Ontario and McMaster Universities osteoarthritis index (WOMAC), pain intensity (as measured with 100 mm VAS) and patient's and physician's assessment of disease severity index were the primary outcome measures of the study. Results: As compared to the baseline, significant decreases were observed in both groups in terms of WOMAC, pain intensity, and disease severity index scores. The improvements were found to be superior in the study group as compared to the controls. Moreover, a significant number of patients in the study group had minimal clinically important improvement when compared to the control group. Conclusion: Mud pack treatment significantly improves the pain and functional status of patients with knee OA. (Turk J Rheumatol 2009; 24: 72-6)